Resveratrol improves ovarian state by inhibiting apoptosis of granulosa cells - Ying Liang; Mei-Ling Xu; Xing Gao; Yan Wang; Li-Nan Zhang; Ya-Cong Li; Qing Guo (Taylor & Francis Group, 2023)
Aim Among the natural polyphenolic compounds, resveratrol (RES) is known for reducing the effects of declining reproductive power through resisting senility, anti-oxidant and anti-inflammatory, while the molecular mechanism of RES in human ovaries is unclear. We aimed to evaluate the most likely mechanisms of RES against apoptosis induced by H2O2 in human ovary granulosa cells.Methods Ovarian granulosa cells from infertile women (≤35 years old) were collected. Those patients defined as polycystic ovary syndrome (PCOS), poor ovarian responder (POR) and Endometriosis were excluded. Then they were randomly divided into control group, model group and the treatment group. Cellular apoptosis was analyzed by flow cytometer method. The related protein and mRNA expressions were detected by western blot and RT-PCR.Results Apoptosis rates of the treatment group containing RES with concentrations of 1 μM and 10 μM were significantly decreased (p < 0.001). Western blot results demonstrated that the proteins levels of transforming growth factor-β (TGF-β), Bax and Caspase 9 were decreased, and Bcl-2 was increased under RES treatment, while the protein levels of Caspase 8, Caspase 3, growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15) expressed no significant difference. The results by RT-PCR of follicle and ovarian development related mRNA factors were consistent with that of western blot assay.Conclusion In conclusion, the present study provides the evidence that RES may affects apoptotic factors to protect human ovarian state.